Strategic structuring of the scientific field of Information Literacy in Brazil: integrating networks and institutions - Melo Soares Simeao, Elmira Luzia; Baptista Belluzzo, Regina Celia [UNESP]; Branco Diogenes, Fabiene Castelo; Nunes, Eny Marcelino; Leite, Cecilia (Univ Brasilia, Dept Ciencia Informacao, 2019)
It seeks to highlight the main studies and experiences involving the scientific field that refers to the current scenario of Information Literacy (IL): evidence and importance of studies and research in the field of Information Science in Brazil and the world, the role of national and international partnerships, their trends in the development of science and joint actions of the networks of institutions, such as the Brazilian Institute of Information in Science and Technology, State University of Sao Paulo Julio de Mesquita Filho, University of Brasilia and the National Association of Research and Post-graduation in Information Science the latter being the most important entity for researchers in this area in Brazil, combining integration efforts with other areas of knowledge. In order illustrate your relevance and the relevance of the theme, the experiences with these partnerships are presented, since they deal with practices and lessons learned with the access and use of information from Information Literacy perspective, evidencing the construction of knowledge and its application with intervention in the social reality, highlighting the interactive form in which they act in any dimension of teaching and learning.
Keywords: information literacy; public and private partnerships; information networks